(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The convergence of artificial intelligence (AI) and cybercrime constitutes one of the most consequential security challenges of the twenty-first century. This article provides a comprehensive interdisciplinary analysis of how AI technologies are being operationalised across the full spectrum of cybercriminal activity, encompassing AI-augmented phishing and social engineering, deepfake-enabled financial fraud and political disinformation, autonomous and polymorphic malware, and adversarial attacks targeting AI systems themselves. Drawing on recent empirical research, documented incident cases, and policy developments across multiple jurisdictions, the analysis identifies critical technical and socio-legal gaps in current cybersecurity defences. It further evaluates how AI can be harnessed as a defensive instrument and examines the emerging regulatory landscape, including the EU AI Act (2024), the UK Online Safety Act (2023), and proposed legislative reforms in India. The article concludes with prioritised recommendations for policymakers, the cybersecurity industry, and the research community, arguing that effective governance of AI-enabled cybercrime demands urgent, internationally coordinated action. The analysis contributes to the nascent interdisciplinary field of AI security studies and identifies three empirical research gaps warranting systematic investigation.